THE ENTERTAINMENT WORLD OF MINANGKABAU PEOPLE IN THE EARLY OF THE 20TH CENTURY - Meri Erawati; I Ketut Surajaya; Linda Sunarti (Balai Pelestarian Nilai Budaya Jawa Barat, 2020)
This article discusses the entertainment world of the Minangkabau people in the Dutch colonial epoch. The world of entertainment is constructed using the historical method through the collection of written sources particularly contemporary newspapers and is equipped with books in the form of memoirs and autobiographies. The data obtained are then criticized and synchronized to produce historiography. The results show that the entertainment that developed in Minangkabau is identified into two namely traditional entertainment and modern entertainment. The traditional entertainment is entertainment that has been passed down from the Minangkabau culture, while modern entertainment is entertainment influenced by the West.Artikel ini menjelaskan tentang dunia hiburan masyarakat Minangkabau pada masa kolonial Belanda. Dunia Hiburan dikontruksi menggunakan metode sejarah melalui pengumpulan sumber-sumber tertulis terutama koran-koran yang terbit sezaman serta dilengkapi dengan buku- buku berupa memoar dan autobiografi. Data yang diperoleh kemudian dikritisi dan dikronologikan sehingga menghasilkan historiografi. Hasil penelitian menunjukkan bahwa hiburan yang berkembang di Minangkabau terpola menjadi dua yakni hiburan tradisional dan hiburan modern, dimana hiburan tradisional merupakan hiburan yang telah turun temurun dari budaya masyarakat Minangkabau, sedangkan hiburan modern merupakan hiburan pengaruh Barat.